2008
DOI: 10.1111/j.1440-172x.2008.00683.x
|View full text |Cite
|
Sign up to set email alerts
|

Roles assessment in families of children with chronic renal failure on peritoneal dialysis

Abstract: Families with a child on chronic peritoneal dialysis have to assume a significant burden of care, intensifying the demands and the reorganization of roles in the families of children. The purpose of this study is to describe the implications of role changes in families of children with chronic renal disease on peritoneal dialysis. This is a case study of four families of children with chronic renal disease on peritoneal dialysis. Fourteen family members participate in the study. After the child's chronic kidne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
1
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 16 publications
(16 reference statements)
3
13
1
4
Order By: Relevance
“…This fact makes caring for oneself impossible, which, consequently, compromises the quality of life of these caregivers whose lives are only focused on the needs of the child. Similar results related to the commitment to the quality of life were obtained in studies performed with mothers of children with CKD in Australia 9,13 and in Brazil, 18 due to care overload affecting the primary caregiver who, in most cases, is the mother, and needs to be present with the child in addition to managing the care at home.…”
Section: Living Life For the Childsupporting
confidence: 69%
See 1 more Smart Citation
“…This fact makes caring for oneself impossible, which, consequently, compromises the quality of life of these caregivers whose lives are only focused on the needs of the child. Similar results related to the commitment to the quality of life were obtained in studies performed with mothers of children with CKD in Australia 9,13 and in Brazil, 18 due to care overload affecting the primary caregiver who, in most cases, is the mother, and needs to be present with the child in addition to managing the care at home.…”
Section: Living Life For the Childsupporting
confidence: 69%
“…17 Providing alternative care for the siblings of the sick child, after needing to re-establish relationships with the siblings who felt excluded, abandoned and neglected because they did not receive the same attention. 13,18 In this context, communication is an important factor among family members, since children can perceive this difficult moment and not understand what is happening, and even feel guilty about the circumstance the family is facing. 19 Thus, nursing in primary health care can contribute to the prevention of aggravations caused by communication, creating healthy methods of coping with the chronic condition together with the family, contributing to the improvement in the quality of life of all members by preparing them for the new health condition.…”
Section: ] Because Taking Care Of the Child Is Essential So I Sofmentioning
confidence: 99%
“…In the study, parents consistently reported having a child with CKD as "a pervasive and profoundly negative experience." (22) Other studies have noted pediatric dialysis disrupts family life (23,24), affects parental marriages (23,25,26), parental healthrelated quality of life (HRQOL) (24), parental stress (26)(27)(28)(29), and results in less parental time spent with healthy siblings (30) and more schooling problems in siblings (23). While all of these studies are limited by small sample sizes, future research may provide better guidance.…”
Section: Children and Families With Few Social Resourcesmentioning
confidence: 99%
“…Outros autores destacam a necessidade de um trabalho de apoio e intervenção na família, o que poderá refletir na melhora do desenvolvimento cognitivo da criança portadora de SD (5) . Tratando-se de famílias com crianças em situações crônicas, as enfermeiras precisam avaliar suas experiên-cias e propor intervenções específicas para aumentar a qualidade de vida, estreitar os mecanismos de enfrentamento, manter o bemestar e promover a saúde dos membros da família (7) . Enfermeiras podem ter um importante papel na promoção de resiliência e adaptação nas famílias de crianças com SD, se elas reconhecerem e valorizarem as capacidades naturais das famílias para suportar, sobreviver e prosperar, mesmo na presença de constantes desafios associados à criança com SD (8) .…”
Section: Introdução Introdução Introdução Introdução Introduçãounclassified